Analisis Penerapan Tax Planning Dalam Mengefisiensikan Beban Pajak Penghasilan Pada PT Sentra Daya Madani - Alfariz, Ghandi; Arifin, Syamsul Bahri; Suryani, Yani (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The research aims to analyze application of tax planning in efficiency PT Sentra Daya Madani income tax burden. This research used a descriptive method. Data collection techniques were carried out using documentation, interviews and a literature study. Analysis data by analyzing the commercial financial statement, reconciling fiscal, analyzing fiscal income statement, and making tax planning. The results of this research show that PT Sentra Daya Madani has implemented tax planning, but it has not been optimal, so that the payment of the tax owed is not yet efficient. There are still gaps that can be implemented or exploited to streamline the tax burden paid. The application of tax planning in this research can streamline the tax burden of IDR 9,089,693.